THE NEW LAW "ON EDUCATION" IN NEW UZBEKISTAN AND ITS CONTENT (Web of Teachers: Inderscience Research, 2024)
President Sh. Mirziyoyev signed the new law "On Education". This is definitely an important step for us young people. I must say that the education system should be brought to a new level, because the country will develop if the education system is conducted effectively. Since that day, based on the experience of Japan, Korea, Singapore, Great Britain, Germany, France and other countries, the education system and effective teaching have fundamentally changed. Education is the lifeblood of the country's future. Every country struggles to create a strong education system and improve it regularly.